The making of an epistemic community around the Global Value Chains approach as a new development tool in the 21st century - Trevignani, Manuel Facundo (Papeles de Europa, 2023)
The Global Value Chains approach has become the new development tool in the last two decades since its emergence at the beginning of the century. This work aims, on the one hand, to study the convergence between its main researchers and the international organizations at the time of the practical translation of its theoretical framework, giving rise to the formation of an epistemic community around these ideas. On the other hand, the article analyzes the main limitations, absences and theoretical omissions to understand development in a comprehensive way.